Manipulation of Heat Dissipation Capacity Affects Avian Reproductive Performance and Output - Zagkle, Elisavet; Martinez-Vidal, Paola Alexandra; Bauchinger, Ulf; Sadowska, Edyta T. (Frontiers in Ecology and Evolution, 2022)
Animal life requires hard work but the ability to endure such workload appears to be limited. Heat dissipation limit (HDL) hypothesis proposes that the capacity to dissipate the excess of body heat during hard work may limit sustained energy use. Experimental facilitations of heat loss rate via feather-clipping in free-living birds seem to support HDL hypothesis but testing of HDL through laboratory experiments under controlled conditions is not reported. We employed a two-factorial experimental design to test HDL hypothesis by manipulating the capacity to dissipate heat through exposure of captive zebra finches (Taeniopygia guttata) to a cold and warm ambient temperature (14 and 25 °C), and through manipulation of the insulating layer of feathers around the brood patch in females (clipped and unclipped). To simulate foraging costs encountered in the wild we induced foraging effort by employing a feeding system that necessitated hovering to access food, which increased energetic costs of reproduction despite ad libitum conditions in captivity. We quantified the outcome of reproductive performance at the level of both parents, females, and offspring. Thermal limitations due to warm temperature appeared at the beginning of reproduction for both parents with lower egg-laying success, smaller clutch size and lower egg mass, compared to the cold. After hatching, females with an enhanced ability to dissipate heat through feather-clipping revealed higher body mass compared to unclipped females, and these clipped females also raised heavier and bigger nestlings. Higher levels for oxidative stress in plasma of females were detected prior to reproduction in warm conditions than in the cold. However, oxidative stress biomarkers of mothers were neither affected by temperature nor by feather-clipping during the reproductive activities. We document upregulation of antioxidant capacity during reproduction that seems to prevent increased levels of oxidative stress possibly to the cost of female body condition and offspring growth. Our study on reproduction under laboratory-controlled conditions corroborates evidence in line with the HDL hypothesis. The link between temperature-constrained sustained performance and reproductive output in terms of quality and quantity is of particular interest in light of the current climate change, and illustrates the emerging risks to avian populations.